The Role Of Digital Media In Modern Education - Turopova Lola Suyunovna; Qobulov Umid Saidmurod o’g’li (Euro Asian Journal Publishing, 2025)
Purpose of the article In today's rapidly developing world, digital media has become an integral part of our lives, transforming various fields, including education. With the advent of technology, traditional teaching methods are being revolutionized, creating new opportunities and challenges for teachers and students. It is transforming the traditional environment, offering new ways to engage students and enhance their learning experience. This article aims to explore the global perspective of the impact of digital media on education, highlighting its advantages, challenges, and the future of education in the digital age. These technologies enable students to actively participate in the learning process, develop critical thinking, collaboration, and creativity
Keywords: digital media; impact; knowledge; education